Enhanced Outcomes, Improved Feedback: Maximizing Success Through Collaborative Final Projects in Quantitative Methods Courses - Hansen, Michael A. (Taylor & Francis, 2025)
In political science, teaching quantitative methods can pose challenges due to students’ apprehensions and perceptions of the content, the complexity of the material, and the significant time commitment required from instructors. I advocate for adopting collaborative final projects in quantitative methods courses to mitigate these challenges. A comparative case study analysis is implemented to examine quantitative courses with a collaborative final research project to those with an individual project in two countries: Finland and the United States. There was a noticeable decrease in student anxiety and instructor’s time commitments and an increase in student success and favorable feedback toward the course and instruction. Overall, adoption of collaborative learning into quantitative methods courses can be mutually beneficial for both students and instructors.